An examination of analysis and optimization procedures within a PBSD framework - Cott, Andrew (Kansas State University, 2009)
The basic tenets of performance based seismic design (PBSD) are introduced. This includes a description of the underlying philosophy of PBSD, the concept of performance objectives, and a description of hazard levels and performance indicators. After establishing the basis of PBSD, analysis procedures that fit well within the PBSD framework are introduced. These procedures are divided into four basic categories: linear static, linear dynamic, nonlinear static, and nonlinear static. Baseline FEMA requirements are introduced for each category. Each analysis category is then expanded to include a detailed description of and variations on the basic procedure. Finally, optimization procedures that mesh well with a PBSD framework are introduced and described. The optimization discussion focuses first on the solution tools needed to effectively execute a PBSD multi-objective optimization procedure, namely genetic and evolutionary strategies algorithms. Next, multiple options for defining objective functions and constraints are presented to illustrate the versatility of structural optimization. Taken together, this report illustrates the unique aspects of PBSD. As PBSD moves to the forefront of design methodology, the subjects discussed serve to familiarize engineers with the advantages, possibilities, and finer workings of this powerful new design methodology.
Keywords: Performance based seismic design; Multiobjective optimization; Incremental dynamic analysis; Nonlinear static analysis; Genetic algorithms; Engineering, Civil (0543)